True or False? Keying Direction and Acquiescence Influence the Validity of Socio-Emotional Skills Items in Predicting High School Achievement. Issue 2 (2nd April 2020) - Primi, Ricardo; De Fruyt, Filip; Santos, Daniel; Antonoplis, Stephen; John, Oliver P.
Abstract : What type of items, keyed positively or negatively, makes social-emotional skill or personality scales more valid? The present study examines the different criterion validities of true- and false-keyed items, before and after correction for acquiescence. The sample included 12, 987 children and adolescents from 425 schools of the State of São Paulo Brazil (ages 11–18 attending grades 6–12). They answered a computerized 162-item questionnaire measuring 18 facets grouped into five broad domains of social-emotional skills, i.e.: Open-mindedness (O), Conscientious Self-Management (C), Engaging with others (E), Amity (A), and Negative-Emotion Regulation (N). All facet scales were fully balanced (3 true-keyed and 3 false-keyed items per facet). Criterion validity coefficients of scales composed of only true-keyed items versus only false-keyed items were compared. The criterion measure was a standardized achievement test of language and math ability. We found that coefficients were almost as twice as big for false-keyed items' scales than for true-keyed items' scales. After correcting for acquiescence coefficients became more similar. Acquiescence suppresses the criterion validity of unbalanced scales composed of true-keyed items. We conclude that balanced scales with pairs of true and false keyed items make a better scale in terms of internal structural and predictive validity.